Catastrophism and anxiety are risk factors of chronic pain after total knee arthroplasty: a prospective cohort study - Clara Croppi; Fanny Delaigue; Violaine Guinebertière; Flore Devriese; Pascal Bizot; Jules Descamps; Rémy Nizard; Pierre-Alban Bouché (Bone & Joint Open, 2025)
Aims: After a total knee arthroplasty (TKA), up to 40% of patients suffer from chronic pain. Few studies have focused specifically on psychosocial factors as predictors of chronic pain after TKA. Our study aims to identify psychosocial risk factors of chronic pain after TKA and to identify an optimal threshold for significant scores in the multivariate analysis, using a receiver operating characteristic (ROC) curve. Methods: This was a single-centre prospective study conducted from September 2022 to September 2023, involving 204 patients. The mean age was 70 years (SD 8.59), the mean BMI was 30.49 kg/m2 (SD 5.29), and 70.60% of patients were female (144/204). A form was administered before surgery to collect: Hospital Anxiety and Depression Scale (HADS), anxiety scale State-Trait Anxiety Inventory (STAI)-Y, Amsterdam Preoperative Anxiety and Information Scale (APAIS), Pain Catastrophizing Scale (PCS), and visual analogue scale (VAS). Univariate and multivariate logistic regression was used to determine the risk factors associated with chronic pain. To determine a threshold in the psychological scores associated with chronic pain, ROC curves were performed. Results: A total of 36 patients (17.60%) met the definition of chronic pain, defined as VAS ≥ 4/10 at six months postoperatively. In the multivariate analysis, to be an employee or worker (β = 1.10, 95% CI 0.20 to 2.10, p = 0.018), anxiety STAI-YB (β = 0.03, 95% CI 0.01 to 0.06, p = 0.013), and catastrophism PCS (β = 0.04, 95% CI 0.02 to 0.06, p < 0.001) were associated with chronic pain after TKA. Using ROC analysis, we identified a threshold value of 44.5 for anxiety STAI-YB (sensitivity 57.58%, specificity 74.51%) and of 21.5 for catastrophism PCS (sensitivity 56,25 %, specificity 71.90%) of developing chronic pain after TKA. Conclusion: This study shows that the psychosocial profile of patients can be linked to the occurrence of chronic pain, and underlines the importance of a multidimensional approach to patient assessment and management. Cite this article: Bone Jt Open 2025;6(7):755–763.